Manajemen Pendidikan Karakter dalam Pembinaan Akhlak Mulia di SMP PLUS Al Masduqiah - Eka Sri Wahyuni; Endah Tri Wisudaningsih; Nur Hayati (Journal on Education, 2023)
Education is an awareness that is designed to support the learning environment and the learning process so that learners can actively develop their potential to have spiritual strength, noble character, and the necessary skills themselves, society, nation, and state. In education can not be separated what is called Character Education. According to Fenty Sulasty, there are 18 character values developed, including responsibility, religious, honest, tolerant, discipline, hard work, creative, independent, and democracy. Other values include love of peace, respect for others, love of the motherland, and the spirit of Honor. Researchers use qualitative research with a descriptive approach to explain the phenomena that are happening in SMP Plus Al Masduqiah, which then the information obtained is then interpreted and written in the form of words or descriptive based on facts obtained at the time of the research site. The results of the study were the management of Character Education in the guidance of noble morals in SMP Plus Al Masduqiah through planning and implementation. Implementation of character education in SMP Plus Al Masduqiah such as morning apples, exemplary, learning, control, evaluation. SMP Plus Al Masduqiah requires its students to follow the extracurricular Scout Movement in order to have a good attitude of discipline and integrity.